ANALISIS RESISTENSI TERBUKA TOKOH-TOKOH DALAM NOVEL MARYAM KARYA OKKI MADASARI: KAJIAN RESISTENSI JAMES C SCOTT - Pratiwi, Shuci Rika; Hajrah, Hajrah; Abidin, Aslan (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
This research aims to examine the form of open resistance found in the novel Maryam by Okki Madasari. This research is descriptive qualitative in nature. The data in this research are in the form of words, sentences or discourse that represent resistance contained in the novel Maryam by Okki Madasari with a focus on James C Scoot's study of resistance. The data source in this research is the novel Maryam by Okki Madasari which was published in 2012 and published by the publisher Gramedia Pustaka Utama, Jakarta with a thickness of 280 pages. The results of this research show that there is an open form of resistance carried out by the figures. This resistance was carried out because people always considered themselves and their families to be bad because they had different beliefs from local residents.